Electrospun carbon nanofibers with surface-attached platinum nanoparticles as cost-effective and efficient counter electrode for dye-sensitized solar cells. (January 2015) - Aboagye, Alex; Elbohy, Hytham; Kelkar, Ajit D.; Qiao, Qiquan; Zai, Jiantao; Qian, Xuefeng; Zhang, Lifeng
Abstract: Dye-sensitized solar cells (DSCs) have attracted incredible attention in recent years as relatively inexpensive alternative to silicon solar cells. Conventionally, a transparent fluoride-doped tin oxide (FTO) conductive glass with a thin layer coating of platinum (Pt) is used as counter electrode in DSCs. The widespread use of Pt as counter electrode in DSCs is due to its catalytic capability for I3 - reduction in electrolyte. However, Pt is costly and can be affected by the corrosive nature of I - /I3 - redox couple, which makes it a less desirable candidate for use in industrial scale manufacturing. In this study, carbon nanofibers with surface-attached Pt nanoparticles were prepared by stabilization and carbonization of electrospun polyacrylonitrile (PAN) nanofibers and subsequent controllable Pt nanoparticle growth on the obtained carbon nanofiber surface through redox reaction. The hierarchical carbon nanofibers with surface-attached Pt nanoparticles (ECNFs-PtNPs) were then employed as cost-effective counter electrode in DSCs. The effects of size, morphology, and loading of Pt nanoparticles on performance of DSCs were investigated. Compared to conventional counter electrode, the counter electrode that was made of ECNFs-PtNPs exhibited larger open circuit voltage (Voc ). The DSCs that were made with ECNFs-PtNPs counter electrode demonstrated excellent solar energy conversion efficiencies in the range of 7% to 8%. Graphical abstract: Highlights: Carbon nanofibers with controllable surface-attached Pt nanoparticles (ECNFs-PtNPs) were prepared by electrospinning followed by carbonization and subsequent Pt nanoparticle growth through redox reaction. The hierarchical ECNFs-PtNPs were employed as cost-effective counter electrode in dye-sensitized solar cells (DSCs). The effects of size, morphology, and loading of Pt nanoparticles on performance of DSCs were investigated. DSCs with ECNFs-PtNPs counter electrode demonstrated excellent solar power conversion efficiency which is equivalent or even higher than that of conventional DSCs made with Pt counter electrode.